2021
DOI: 10.3390/cells10030666
|View full text |Cite
|
Sign up to set email alerts
|

Novel Gene Regulation in Normal and Abnormal Spermatogenesis

Abstract: Spermatogenesis is a complex and dynamic processwhich is precisely controlledby genetic and epigenetic factors. With the development of new technologies (e.g., single-cell RNA sequencing), increasingly more regulatory genes related to spermatogenesis have been identified. In this review, we address the roles and mechanisms of novel genes in regulatingthenormal and abnormal spermatogenesis. Specifically, we discussed the functions and signaling pathways of key new genes in mediating the proliferation, different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 146 publications
0
9
0
Order By: Relevance
“…Spermatogenesis is a complex process involving proliferation, differentiation and apoptosis. 54 Activation of the P53 signaling pathway has been shown to induce apoptosis in testicular spermatogenic cells in the presence of high levels of oxidative stress. 55,56 In the current study, we found individual exposure to noise and CO caused apoptosis of germ cells.…”
Section: Discussionmentioning
confidence: 99%
“…Spermatogenesis is a complex process involving proliferation, differentiation and apoptosis. 54 Activation of the P53 signaling pathway has been shown to induce apoptosis in testicular spermatogenic cells in the presence of high levels of oxidative stress. 55,56 In the current study, we found individual exposure to noise and CO caused apoptosis of germ cells.…”
Section: Discussionmentioning
confidence: 99%
“…42,55 Spermatogenesis is a key process in male reproduction, involving many cellular (somatic cell populations, Leydig, Sertoli, and peritubular myoid cells) and molecular (gonadotropins, testosterone, and estrogen) players, which are essential factors in a process that culminates on differentiation of the germinative epithelium to mature sperm cells. 56,57 This complex process can be severely impaired by external conditions, including WD intake and its resulting comorbidities. [11][12][13][14] In general, our WD protocol…”
Section: Discussionmentioning
confidence: 99%
“…DNA and histone methylation contribute to regulate gene expression throughout all spermatogenesis (Carrell, 2019; Du et al, 2021; Rajender et al, 2011). Interestingly, different aspects of lifestyle such as diet, toxicant exposure, air pollution, smoking, or work conditions affect the pattern of DNA and histone methylation, in human and mouse models, which may impact in the etiology of sperm pathologies such as globozoospermia (Comhaire et al, 2017; Dong et al, 2017; Lu et al, 2019).…”
Section: The Round‐headed Spermatozoamentioning
confidence: 99%